2020
DOI: 10.3390/ijms21207444
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Xanthine Oxidase in CKD Progression Associated with Hypercholesterolemia

Abstract: In the present study, we investigated the effects of xanthine oxidase (XO) inhibition on cholesterol-induced renal dysfunction in chronic kidney disease (CKD) mice, and in low-density lipoprotein (LDL)-treated human kidney proximal tubule epithelial (HK-2) cells. ApoE knockout (KO) mice underwent uninephrectomy to induce CKD, and were fed a normal diet or high-cholesterol (HC) diet along with the XO inhibitor topiroxostat (1 mg/kg/day). HK-2 cells were treated with LDL (200 µg/mL) and topiroxostat (5 µM) or sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Since XOR is involved in intracellular UA production, the results of those genetic studies may underlie a critical role of intracellular UA production, instead of SUA, in the development and progression of hypertension. Supporting this hypothesis, plasma XO activity has been associated with CV outcomes, independently of SUA levels [ 98 , 99 ]. In addition, Boban et al showed that XOR was upregulated in subjects with essential hypertension [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since XOR is involved in intracellular UA production, the results of those genetic studies may underlie a critical role of intracellular UA production, instead of SUA, in the development and progression of hypertension. Supporting this hypothesis, plasma XO activity has been associated with CV outcomes, independently of SUA levels [ 98 , 99 ]. In addition, Boban et al showed that XOR was upregulated in subjects with essential hypertension [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular levels might be higher in the setting where synthesis is stimulated, such as may be observed with high xanthine oxidoreductase (XO) activity. Plasma XO activity is associated with CKD progression and cardiovascular outcomes, independently of serum uric acid 45,46 . This could potentially explain why serum uric acid may not predict CKD by Mendelian randomization studies, as the polymorphisms in urate transporters Hyperuricemia is thought to cause kidney injury by both crystal-dependent and crystal-independent mechanisms 48 (Figure 1).…”
Section: Epidemiology Of the Associationmentioning
confidence: 99%
“…In this current Special Edition, thirteen original research articles are presented: twelve in vivo studies in a murine or rat model and one in vitro study [ 3 ]. Seven studies show results from AKI models [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], five from fibrosis models (or CKD models) [ 9 , 11 , 12 , 13 , 14 ] and two from a transplant rejection model [ 4 , 15 ] (two studies used two different in vivo models).…”
mentioning
confidence: 99%
“…Others investigated the role of xanthine oxidase (XO) in CKD progression associated with hypercholesterolemia [ 13 ]. The authors used a murine model of uninephrectomy to induce CKD, in addition to a high-cholesterol diet with a XO inhibitor, and, also, evaluated the results in an in vitro model using immortal tubular epithelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation